Implementation of KKN as Community Service Activities in accordance with the Field of Science: Implementasi KKN sebagai Kegiatan Pengabdian kepada Masyarakat sesuai dengan Bidang Ilmu - Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
Real Work Lecture (KKN) is an intracurricular form which is an implementation of the Tridharma of Higher Education to provide students with work and study experience in community empowerment. Law of the Republic of Indonesia Number 12 of 2012 concerning Higher Education in article 1 paragraph 9 states that Tridharma is the obligation of Higher Education to organize Education, research and community service. Then it is also explained in paragraph 11 that community service is an activity of the academic community that utilizes science and technology to promote people's welfare which educates the life of the nation. In tertiary institutions the implementation of community service will be carried out by students in the form of Real Work Lectures (KKN). Real work lecture activities are a golden opportunity for smart, critical, innovative and creative students in finding the right solutions, formulas and strategies for various problems of unproductive business units/MSMEs and existing development in the village. Placement of many KKN student locations is directed at villages that have superior potential but still lack community skills in managing their natural products. This is a challenge in itself for the group of real lecture participants to change the superior potential of existing villages to have economic value through community empowerment work programs which will be directly assisted by practitioners and the academic community. Students who carry out KKN activities are carried out to mobilize the community in development through various activities that can involve, include, and foster a sense of community ownership of development. KKN is carried out interactively and synergistically between students and the community. Involvement starts from the planning of field activity programs and implementation. Thus students must be empathetic and participatory.